Indonesia’s Fiscal Decentralization Agility to the COVID-19 Pandemic - Nunung Runiawati; Heru Nurasa; ida Widianingsih (Aliansi, 2022)
As one of the countries with the highest total cases in Asia, the Indonesian Government has imposed restrictions on the mobility of people to reduce the spread of the covid-19 virus. The policy has an impact on social and economic aspects. In economic activities, there is a decrease in purchasing power and production power that thus far has not yet been stable has caused an increase in the poverty rate in Indonesia in the last two years. The central and local governments have made some policies to recover the national economy. The demand for the elasticity of those policies is very high, considering that there has been a change in the spreading behavior of the covid-19 virus over the last year. This research discusses the policy on fiscal decentralization to recover the national economy during the Covid-19 pandemic in Indonesia. The research method is based on the analysis of literature studies relevant to this research. The result of the research shows that there are some agile policies on fiscal decentralization during the Covid-19 pandemic, among other things, support for regions in handling the covid-19 pandemic, support for regions in fulfilling service facilities and infrastructure, support for regions in improving regional performance, support for regions in the implementation of asymmetric decentralization and new autonomous regions and support for the village.  Thus far, the imposed policies on fiscal decentralization have been able to decrease the active cases of covid-19, but the policies require a continuous evaluation to be able to produce integrated policies on fiscal decentralization in the future.